ASAP: PENEGAKAN HUKUM LINGKUNGAN YANG TUMPUL TERHADAP KORPORASI WILAYAH TITIK API DI INDONESIA - Sommaliagustina, Desi (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2017)
Forest and Peatland fires that hit several provinces in Indonesia last year. One proof that environmental laws do not go according as it should. As was the case in the province of Riau, South Sumatra, Jambi, West Kalimantan and Central Kalimantan. The case of forest fires and haze become routine every year. Ironically, despite the smoke haze repeated every year with huge losses, the handling remains the same. Reactionary and tend to dwell on purely technical matters outage. The country had neglected its obligations. The fundamental problem of forest fires and land mismanagement of natural resources that have been perpetuated by bad practices, including the monopoly on possession. All these bad practices perpetuated through the legitimacy of such a permit. Disaster fumes resulting from bad practices do  corporations  with  a  common  pattern.  To  keep  production  costs  down,  the company burned land when land clearing. This is clearly contrary to the Law No. 32/2009 on the Protection and Environmental Management. Companies that obtain permission means subject to the terms and provisions of the law governing how they should be tried, including in it should not be burned, and shall keep the region. If all violations was systematic, it was because there was never any enforcement against corporations in the region found api.Point of views of the repeating pattern of the company which is intentionally doing bad practices that lead to ecological disaster, it can be said that the corporation has done of serious crimes, due to meet the elements of a planned and widespread.